Ritual Ratibu dalam Upacara Kematian pada Masyarakat Suku Muna di Kabupaten Muna - La Salimu . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
The purpose of this study is to know and describe the procession of the implementation of ratibu ritual on Muna tribe community. In addition, this study is also aimed to describe and interpret the meaning of symbols of objects contained in the implementation of ratibu ritual of people in Muna tribe. This study uses descriptive qualitative data, where researchers try to give an idea of the procession of the implementation of ratibu ritual and interpret the symbolic meaning of objects in the spiritual process of ratibu ritual by community of Muna tribe. The results of this study indicate: (1) The implementation of procession of ratibu ritual in Muna tribe community is carried out in three stages, namely (a) Kafongkorano ratibu (opening of the implementation of ratibu) held on the second night after the dead bodies are buried, Poratibu (implementation of the ratibu), which is performed in a special room within a mosquito net and performed for 27 times at each time of the five-day prayer. The core activity of the lebe performing the Ratibu ritual in the mosquito net is to read the sentence